Trends in stroke-related mortality in atrial fibrillation patients in the United States: Insights from the CDC WONDER database - Muhammad Abdullah Naveed; Sivaram Neppala; Himaja Dutt Chigurupati; Muhammad Omer Rehan; Ahila Ali; Hamza Naveed; Bazil Azeem; Rabia Iqbal; Manahil Mubeen; Mashood Ahmed; Ayman R. Fath; Timir Paul; et al. (American Heart Journal Plus)
Background: Stroke associated with atrial fibrillation (AF) is a significant cause of mortality. This study analyzed demographic trends and disparities in mortality rates due to stroke in AF patients aged ≥25 years. Methods: A retrospective analysis was conducted to acquire death data using the Centers for Disease Control and Prevention database from 1999 to 2020. Age-adjusted mortality rates (AAMRs) were calculated per 100,000 persons, and trends were assessed using Average Annual Percentage Change (AAPC) and annual percent change (APC). Data were stratified by year, sex, race/ethnicity, and geographical regions. Results: Between 1999 and 2020, AF-associated stroke contributed to 331,106 deaths among adults in this study population. Deaths occurred predominantly in medical facilities (43.2 %). The overall AAMR for AF-associated stroke decreased from 7.4 in 1999 to 6.4 in 2020, with an APC of −1.02 (p-value = 0.004). Additionally, AAMR showed a significant decline from 2015 to 2018 with an APC of −7.22 (p-value <0.000001), followed by a striking rise from 2018 to 2020 (APC: 4.98) (p-value = 0.0008). Women had slightly higher AAMR than men (men: 6.6; women: 7.1) (p value = 0.02). AAMRs varied among racial/ethnic groups, with Whites having the highest AAMR (7.4), followed by Blacks (5.4), American Indian or Alaska Natives (4.6), Asian or Pacific Islanders (4.5), and Hispanics (4.1). AAMRs decreased for all races except Blacks. Geographically, AAMRs ranged from 4.3 in Nevada to 11.9 in Vermont, with the Western region showing the highest mortality (AAMR: 7.9). Nonmetropolitan areas had slightly higher AAMRs than metropolitan areas, with both experiencing a decrease over the study period. Conclusion: This analysis depicts significant demographic and geographic disparities in mortality rates attributed to stroke associated with AF. Targeted interventions and equitable healthcare access are crucial to mitigate these disparities and improve outcomes for this population.